2014
DOI: 10.1002/hep.26564
|View full text |Cite
|
Sign up to set email alerts
|

Detection of anti-isoniazid and anti-cytochrome P450 antibodies in patients with isoniazid-induced liver failure

Abstract: Isoniazid (INH)-induced hepatotoxicity remains one of the most common causes of drug-induced idiosyncratic liver injury and liver failure. This form of liver injury is not believed to be immune-mediated because it is not usually associated with fever or rash, does not recur more rapidly on rechallenge, and previous studies have failed to identify anti-INH antibodies. In this paper we found antibodies present in the sera of 15/19 cases of INH-induced liver failure. Anti-INH antibodies were present in 8; 11 sera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 22 publications
(41 reference statements)
3
97
0
1
Order By: Relevance
“…Hepatic enzyme N-acetyltransferase 2 acetylates INH to acetylisoniazid which is first hydrolysed to acetylhydrazine and subsequently oxidized by CYP2E1 to produce hepatotoxic intermediates. 18 Metushi et al reported that INH is bioactivated by, and covalently binds to, CYP2E1, in the presence of a NADPH regenerating system 22 and the data of this study was found to be consistent with the observation that the high activity variant CYP2E1 c1/c1 genotype is associated with more severe liver injury. 21 In this study, we found that the HO-1 is important in protecting E47 cells against INH-RMP induced toxicity.…”
Section: Discussionsupporting
confidence: 89%
“…Hepatic enzyme N-acetyltransferase 2 acetylates INH to acetylisoniazid which is first hydrolysed to acetylhydrazine and subsequently oxidized by CYP2E1 to produce hepatotoxic intermediates. 18 Metushi et al reported that INH is bioactivated by, and covalently binds to, CYP2E1, in the presence of a NADPH regenerating system 22 and the data of this study was found to be consistent with the observation that the high activity variant CYP2E1 c1/c1 genotype is associated with more severe liver injury. 21 In this study, we found that the HO-1 is important in protecting E47 cells against INH-RMP induced toxicity.…”
Section: Discussionsupporting
confidence: 89%
“…As discussed in the Introduction, there are multiple lines of evidence that INH-induced liver injury in patients is immune-mediated, and a reactive metabolite of the parent drug is responsible (Metushi et al, 2011(Metushi et al, , 2012(Metushi et al, , 2013. Mice represent a better model for the metabolism of INH in humans than rats because blood levels and covalent binding of INH were higher in mice vs rats (Metushi et al, 2012); therefore, we attempted to develop an animal model of INH-induced liver injury in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, T-cells from patients with mild INH-induced liver injury proliferate when incubated with INHmodified proteins, while T-cells from patients with severe INH-induced liver injury also proliferate when incubated with INH alone (Warrington et al, 1978(Warrington et al, , 1982. In addition, most patients with INH-induced liver injury have antibodies against either INH-modified proteins or the cytochromes P 450 that bioactivate INH (Metushi et al, 2013). Taken together, these data suggest that INH-induced liver injury is immune-mediated, as reviewed elsewhere (Metushi et al, 2011), and mice are more likely to be a model for INH-induced liver injury in humans than rats.…”
Section: Introductionmentioning
confidence: 99%
“…These were not found in isoniazid-treated controls, which suggests that if a humoral response is detected, adduct formation must be involved. 73 Finally, we have recently isolated T-cells from patients with iDILI to generate isoniazid-specific T-cell clones (unpublished data).…”
Section: Isoniazidmentioning
confidence: 99%